The Hidden Blackbox: Corrective Rape Against Lesbian, Bisexual (Women) and Male Transgender - Agustine, Sri (Jurnal Perempuan, 2021)
This article discusses about the corrective rape against lesbian, bisexual (women), and male transgender that is performed by the perpetrator with aim to correct the LBT’s (lesbian, bisexual, and transgender) sexuality. Such sexuality that are deemed bad, abnormal and cursed, therefore must be corrected. Corrective rape is perceived as a form of punishment, and it is everyone’s responsibility to undertake correction. Corrective rape has rarely been revealed. In order to reveal the facts about corrective rape against LBT in Indonesia, this article writes the stories of four LBTs that would open up our conscience, that any form of corrective rape must be abolished, in line with our hope to abolish sexual violence against women through the legislating of the draft law on the abolition of sexual violence (RUU PKS).